Accelerating electric vehicle uptake: Modelling public policy options on prices and infrastructure. (August 2022) - Broadbent, Gail Helen; Allen, Cameron Ian; Wiedmann, Thomas; Metternicht, Graciela Isabel
Highlights: We model policy options to accelerate passenger Battery EV diffusion in Australia. Meeting recharger deployment targets as fleet grows is crucial to reach 100% uptake. Subsidising BEV purchase brings forward price-parity tipping point. Recharger and vehicle rebate policies costing AUD37.4 billion speed up transition. Emissions reduction is best when policy introduced at earliest possible date. Abstract: Transitioning to passenger battery electric vehicles (BEV) can mitigate climate change impacts of road transportation. We develop a novel BEV policy model, nesting it within a national-scale macroeconomic system dynamics model ( iSDG-Australia ) to simulate a suite of policy pathways. We model combinations of infrastructure support and subsidies, which bring forward the price-parity tipping point, thus rapidly accelerating BEVs' share of new car sales. However, ongoing complementary charging infrastructure investment is critical to reach 100% new BEV car sales by 2050 in Australia. Even with a rapid transition, the modelled fleet would not achieve net-zero greenhouse gas emissions by 2050 due to vehicle longevity; and suddenly ceasing financial incentives could retard BEV sales by a decade. Based on our assumptions, results suggest emissions reductions are maximised by the fastest transition of the passenger vehicle fleet to BEVs, entailing government policy support from 2020 to 2050, for both adequate infrastructure deployment (AUD17.9b) and vehicle rebates (AUD19.5b), which achieves earlier BEV price-parity with fossil-fuelled vehicles.